2022
DOI: 10.1155/2022/1122494
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Ameliorates Diabetic Cardiomyopathy via Attenuating Oxidative Stress and Improving Mitochondrial Function

Abstract: Diabetic cardiomyopathy (DCM) is considered to be a critical contributor to the development of heart failure. Empagliflozin (EMPA), a sodium-glucose cotransporter 2 inhibitor, has been shown to prevent cardiovascular events and reduce the incidence of heart failure in randomized clinical trials. However, the mechanism of how EMPA prevents DCM is poorly understood. To study the potential mechanisms involved in the therapeutic effects of EMPA, we assessed the protective effects of EMPA on myocardial injury in ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Another antioxidative property presented by empagliflozin involves suppressing NOX4 and attenuating oxidation products. The study by Wang et al showed an intensified expression of Nrf2 and HO-1 protein, which was impaired in non-treated diabetic groups, and the promotion of Nrf2 nuclear translocation in the empagliflozin group [ 83 , 110 ]. Wang et al also described cardio-protective effects of empagliflozin treatment studied in both db/db mice and palmitate-exposed H9C2 cardiomyocytes, which include attenuating of cardiac remodelling, increasing sensitivity to insulin and supporting mitochondrial activity.…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another antioxidative property presented by empagliflozin involves suppressing NOX4 and attenuating oxidation products. The study by Wang et al showed an intensified expression of Nrf2 and HO-1 protein, which was impaired in non-treated diabetic groups, and the promotion of Nrf2 nuclear translocation in the empagliflozin group [ 83 , 110 ]. Wang et al also described cardio-protective effects of empagliflozin treatment studied in both db/db mice and palmitate-exposed H9C2 cardiomyocytes, which include attenuating of cardiac remodelling, increasing sensitivity to insulin and supporting mitochondrial activity.…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
“…Wang et al also described cardio-protective effects of empagliflozin treatment studied in both db/db mice and palmitate-exposed H9C2 cardiomyocytes, which include attenuating of cardiac remodelling, increasing sensitivity to insulin and supporting mitochondrial activity. The ability to promote Nrf2 is one of the factors that determines antioxidative properties of empagliflozin and, overall, stands for a compound process of preventing diabetic cardiomyopathy [ 110 ].…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
“…To further analyze the role of genes in pathways, Hub genes were mapped in the KEGG pathways. A total of 28 rats were randomly divided into three groups: normal control group (8), diabetic group (10), and YJHD group (10). To construct the diabetic rat models, streptozotocin dissolved in citric acid solution was injected into the peritoneal cavity of the rats in the diabetic and YJHD groups at a dose of 60 mg/kg [12].…”
Section: Enrichment Analysismentioning
confidence: 99%
“…Pathological changes in DCM include myocardial fbrosis, left ventricular hypertrophy, and impaired left ventricular systolic and diastolic function. Without effective treatment, these pathological changes will eventually lead to cardiac dysfunction, heart failure, and even death [8,9]. At least about 30% of diabetic patients sufer from DN [10].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence have identified the antioxidant properties of empagliflozin [ 5 ]. In vivo experiments have shown that empagliflozin plays a cardioprotective role by impeding inflammatory responses and myocardial fibrosis in human hearts, and therefore, prevents the progression of diabetic cardiomyopathy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%